Myo/Nog cells are present in the ciliary processes, on the zonule of Zinn and posterior capsule of the lens following cataract surgery. (June 2018) - Gerhart, Jacquelyn; Withers, Colleen; Gerhart, Colby; Werner, Liliana; Mamalis, Nick; Bravo-Nuevo, Arturo; Scheinfeld, Victoria; FitzGerald, Paul; Getts, Robert; George-Weinstein, Mindy
Abstract: Myo/Nog cells, named for their expression of MyoD and noggin, enter the eye during early stages of embryonic development. Their release of noggin is critical for normal morphogenesis of the lens and retina. Myo/Nog cells are also present in adult eyes. Single nucleated skeletal muscle cells designated as myofibroblasts arise from Myo/Nog cells in cultures of lens tissue. In this report we document the presence of Myo/Nog cells in the lens, ciliary body and on the zonule of Zinn in mice, rabbits and humans. Myo/Nog cells were rare in all three structures. Their prevalence increased in the lens and ciliary body of rabbits 24 h following cataract surgery. Rabbits developed posterior capsule opacification (PCO) within one month of surgery. The number of Myo/Nog cells continued to be elevated in the lens and ciliary body. Myo/Nog cells containing alpha smooth muscle actin and striated muscle myosin were present on the posterior capsule and overlaid deformations in the capsule. Myo/Nog cells also were present on the zonule fibers and external surface of the posterior capsule. These findings suggest that Myo/Nog contribute to PCO and may use the zonule fibers to migrate between the ciliary processes and lens. Highlights: Myo/Nog cells are present in low numbers in the lens, ciliary body and on the zonule of Zinn in mice, rabbits and humans. The prevalence of Myo/Nog cells increased in the lens and ciliary processes following cataract surgery. Myo/Nog cells contribute to posterior capsule opacification. Myo/Nog cells containing alpha smooth muscle actin and striated muscle myosin overlaid wrinkles in the posterior capsule. Myo/Nog cells may use the zonule fibers to migrate between the ciliary processes and lens.